INTEGRATION AND ADAPTATION OF FOREIGN STUDENTS IN THE URBAN ENVIRONMENT OF SOCHI (BASED ON THE EXAMPLE OF TURKMEN) - Belozerova, Marina Vital'evna (History, Archeology and Ethnography of the Caucasus, 2025)
The purpose of the study is to identify the mechanisms for the formation of communication connections, integration and adaptation of Turkmen students to the urban environment of Sochi.  They study at the Sochi Institute (branch) of the RUDN University. Migration has social consequences. They manifest themselves in processes: the socio-cultural life internationalization, the emergence of crisis phenomena in the economy and others. Therefore, the task of studying these processes among foreign students, regardless of their ethnic, religious, ideological, and social affiliation, is relevant. The results of the study allow us to analyze experience at the regional level. This experience is relevant at the stages of management decisions development, adoption and implementation. The principles of systemic and process approaches, comparative typological and comparative analysis, methodological approaches of «securitization» and «case study» were used in the study, methodological approaches of «securitization» and case-studies were used. The sampling method made it possible to determine a group of students (Turkmens), to carry out the research on a chronological basis (2023-2024) and a territorial principle (the city of Sochi, Krasnodar region) – «a case». The study used special methods: questionnaires and interviews, the method of primary statistical data processing, and the technique of reflecting the obtained indicators in the form of diagrams. An analysis of sources is given: published legislative acts of the Russian Federation and Turkmenistan on the problems of educational migration and the results of a questionnaire survey, interview data. Conclusions are drawn on this basis. This is a fast pace of adaptation of Turkmen students to the conditions of a foreign language and foreign cultural environment in the city. The factors that shaped social communications were identified: studying in groups with a mixed ethnic composition, the distance of the university from the place of residence and others. The reasons for the misunderstanding between the Turkmens and the local population are shown in the article. Attention is focused on the issue of the possibility of forming a Turkmen diaspora in Sochi.
Keywords: educational migration; Turkmen students; a higher educational institution; integration; adaptation; intercultural communications; Sochi; questioning; interviewing